Elderly caregiver: analyzing the backgrounds and training of students who finished their elderly caregiver course - Faht, Gercino; Vieira de Araújo Sandri, Juliana (O Mundo da Saúde, 2016)
The objective of this research was to identify and reflect about the training and capabilities of the elderly caregivers, the institution where the search was developed take place in the city of Curitiba, State of Paraná. An Institution who offer the specific course for people wants to work as elderly caregiver. All the information collected came from documents and registers of the two last grades of the year 2012, It represents the amount of 55 fifty-five students. The results show that women predominate this universe, full high school education and average age around 45 years. The study found that 14 graduates work as a private home for elderly caregivers, 9 graduates working in long-stay institutions for the elderly and other 3 graduates take care of their own elderly family. This article as well as indicating who are these caregivers of the elderly, also presents how was the process of its formation, and to achieve this purpose, it was necessary to insertion of the researcher in educational institution, where it examined relevant documents to contribute to the composition of this profile.